The Contribution of Teaching Factory Program Implementation on Work Readiness of Vocational High School Students In Makassar - Dewi, Shabrina Syntha; Sudira, Putu (Universitas Negeri Makassar, 2018)
This study aims to reveal the contribution of teaching factory program implementation on work readiness of Vocational High School (VHS) students in Makassar. The research method used is quantitative approach with causal comparative. The population in this research is the students of VHS class XII in Makassar of academic year 2017/2018 who have carried out the work practice in teaching factory. The sample of 140 students is determined by proportional random sampling technique. Data analysis technique used is descriptive and inferential statistic analysis. The results showed that there is a significant influence between the contribution of teaching factory program implementation on work readiness of vocational high school students in Makassar with a contribution of 34.6%. These results indicate that the implementation of the teaching factory program of vocational high schools should be optimized to improve the work readiness of vocational high school students so that the level of employment of vocational graduates is increasing.